Management Experience of Subglottic Stenosis by Endoscopic Bougie Dilatation with Mitomycin C and Review of Literature: Case Series - Liew, Y. T. (Indian J Otolaryngol Head Neck Surg, 2014)
The aim of the study was to examine and analyze the epidemiology and outcome of treatment for paediatric acquired subglottic stenosis treated with endoscopic bougie dilatation and topical mitomycin C. There were 15 patients identified from 2008 until 2013. All of them had acquired subglottic stenosis due to history of intubation. Majority of the patients had grade III stenosis, with the total of seven. Three patients had grade IV; three were grade II and two were grade I. All of the patients with severe stenosis (grade III and IV) needed tracheostomy while only one in mild stenosis group (grade I and II) required it for prolonged ventilation rather than obstruction due to subglottic stenosis. All of them underwent direct laryngoscopy under general anesthesia followed by endoscopic dilatation with bougie and topical mitomycin C 0.4 mg/ml for 5 min. Aim of success in our study was decannulation of tracheostomy or absence of symptoms at exertion. We achieved 6 (60 %) successful decannulation out of 10 patients with tracheostomy (excluded the patient with tracheostomy in grade I stenosis due to prolonged ventilation). As for those without tracheostomy, 3 (75 %) out of 4 patients were asymptomatic even at exertion. Average number of dilatation was 3.1 times, with mean duration of 28 min. No complications were reported in our series. One patient with grade I stenosis passed away due to severe pneumonia unrelated to the stenosis or dilatation, and she did not have any dilatation before she passed away. Multiple related risk factors were identified such as intubation, prematurity, movement of endotracheal tube, respiratory infection, traumatic intubation and gastroesophageal reflux disease. Experience of open surgical method was very limited in our centre in Sabah in East Malaysia. Endoscopic technique plays an important role in treatment of subglottic stenosis with adjunct like mitomycin C possibly booster the successful rate.